Complete degradation of polycyclic antibiotic methacycline by a micro/nanostructured biogenic Mn oxide composite from engineered Mn(II)-oxidizing Pseudomonas sp. MB04B - Jie Zeng; Zhenghu Tong; Zhi Li; Yongxuan Liu; Li Xie; Tan Wang; Shiwei Li; Lin Li (Microbiology Spectrum)
ABSTRACT The misuse and improper disposal of methacycline (MTC), a widely used broad-spectrum antibiotic in human clinical settings and livestock production, poses significant threats to both human health and the ecological environment. In this study, a wild-type Mn(II)-oxidizing Pseudomonas strain MB04B was modified through multiple gene deletions, leading to a maximum 35% increase in Mn oxide deposit amount (MnODA) in the engineered strain MB04R-14, and accelerated formation of biogenic Mn oxide (BMO) aggregates, which exhibited the capability to degrade and detoxify MTC completely. After constructing a mini-Tn5 transposon insertion mutant library and screening for MnODA-increased mutants, a total of 10 target genes located in the corresponding mutant loci were identified using the high-efficiency thermal asymmetric interlaced PCR (hiTAIL-PCR) method. These genes were systematically knocked out singly or in multiple combinations, and the highest MnODA-promoted mutant (MB04R-14) was obtained, in which seven genes were knocked out. Following the characterization of the BMO aggregate complex formed in MB04R-14 as a micro-/nanostructured ramsdellite (MnO2) composite through means of several analysis methods, the complex was assessed for MTC degradation under laboratory trials. Complete MTC degradation was revealed after 24 h of treatment with the BMO complex, and the metal ions Mg2+, Cu2+, Ni2+, and Co2+ significantly inhibited MTC degradation efficiency. Liquid chromatography-mass spectrometry identified three intermediates in the degradation pathway, and a possible degradation-metabolic pathway of MTC by the BMO complex was proposed. Finally, the residual antibiotic activity, continuous degradation cycle performance, and treatment of MTC-containing hospital wastewater were evaluated.IMPORTANCEDue to the common usage and recalcitrance to degradation, methacycline is often found in various surface water and wastewater as a persistent antibiotic toxicant, posing significant risks to the environment and public health. By engineering a Pseudomonas strain, we developed a dynamic oxidative composite comprising engineered Pseudomonas cells and biogenic Mn oxides. This system not only enhances oxidative capacities but also accelerates the formation of biogenic Mn oxides, leading to the complete degradation of methacycline. The findings highlight the potential of engineered Pseudomonas strain as a sustainable solution for mitigating antibiotic pollution, thereby contributing to cleaner water resources and protecting ecosystems.